BS EN ISO 52016-3. Energy performance of buildings. Energy needs for heating and cooling, internal temperatures and sensible and latent heat loads. Part 3. Calculation procedures regarding adaptive building envelope elements (5th May 2022) - British Standards Institution,
No abstract available